Towards new paradigms: multiple pathways for the Arabian Neolithic. (18th April 2013) - Crassard, Rémy; Drechsler, Philipp
Abstract : The origin and course of the Neolithic on the Arabian Peninsula is the subject of an ongoing academic debate. Faunal data suggest an origin for domestication of animals in the Levant and these can be found in Arabia from the sixth millennium onwards. In contrast, lithic evidence does not support the hypothesis that Neolithic herders, accompanying their herds, spread over the entire Peninsula, as they did not leave significant traces of their material culture. Although Pre‐Pottery Neolithic A (PPNA)/PPNB influences can be traced across the northern part of Arabia, it is barely possible to observe them further south. By contrast, lithic technology in this region is characterised by major indigenous developments that might originate from a Pleistocene cultural heritage. By discussing the process of Neolithisation in Arabia from different points of view we can avoid the pitfalls of simplistic or monocausal models as well as preconceptions. Furthermore, we will be able to demonstrate that the Neolithic developed differently in different regions of the Arabian Peninsula.